2022
DOI: 10.3329/bjms.v21i4.60262
|View full text |Cite
|
Sign up to set email alerts
|

Khamira Banafsha for the symptomatic treatment of Covid-19 Disease

Abstract: Respiratory illness is one of the most important public health problems in many countries worldwide. Even though most of the ailments are treatable with normal care, respiratory-related mortality continues to increase year after year. The global situation is deteriorating as a result of the COVID-19 epidemic. Numerous Unani formulations are beneficial against a variety of respiratory disorders, but they must be clinically researched before they can obtain widespread acceptance in the modern world. At the momen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The content validity index is the approach for content validity that is most frequently mentioned in instrument development studies 30 . Panel members are asked to rate instrument items on a 4-point ordinal scale (1 [not relevant], 2 [somewhat relevant], 3 [quite relevant], and 4 [highly relevant]) based on their clarity and relevance to the study's underlying construct as defined by theoretic definitions of both the constructs itself and its dimensions 31,32,33 . The I-CVI calculations for the relevancy of each item are as follows.…”
Section: Discussionmentioning
confidence: 99%
“…The content validity index is the approach for content validity that is most frequently mentioned in instrument development studies 30 . Panel members are asked to rate instrument items on a 4-point ordinal scale (1 [not relevant], 2 [somewhat relevant], 3 [quite relevant], and 4 [highly relevant]) based on their clarity and relevance to the study's underlying construct as defined by theoretic definitions of both the constructs itself and its dimensions 31,32,33 . The I-CVI calculations for the relevancy of each item are as follows.…”
Section: Discussionmentioning
confidence: 99%
“…2 Previous researches has identified a strong correlation between vitamin D insufficiency and a number of prevalent chronic illnesses like diabetes, asthma, and rheumatoid arthritis that are characterised by elevated inflammatory response and immune system dysfunction. 3,4 Aside from the aforementioned benefits, vitamin D levels are being studied in relation to oral health issues such as dental caries, periodontitis. 5 Vitamin D, sometimes called as the "sunshine" vitamin, is a critical subject that has drawn the interest of many researchers and the general public in recent decades, as a sizable part of the…”
Section: Introductionmentioning
confidence: 99%
“…18 Recently it has been reported that Malassezia species caused invasive bloodstream infection in immune-compromised patients. 19 Immunomodulation by Unani herbal preparations may be advised in such patients 20 . PV may be a comorbid condition in H. pylori infected patients.…”
Section: Introductionmentioning
confidence: 99%